The impact of cardiopulmonary resuscitation (CPR) training on schoolchildren and their CPR knowledge, attitudes toward CPR, and willingness to help others and to perform CPR: mixed methods research design - Sanela Pivač; Primož Gradišek; Brigita Skela-Savič (BMC, 2020)
Abstract Background The benefits of cardiopulmonary resuscitation training for schoolchildren are well known, but the appropriate age for introducing training is still being discussed. This is a very important issue, since out-of-hospital cardiac arrest is a major public health concern. The objective of this study was to investigate the effects of implemented cardiopulmonary resuscitation training on the knowledge of schoolchildren in the last three grades of Slovenian elementary schools and theirs willingness, attitudes, and intentions toward helping others and performing cardiopulmonary resuscitation. The experience of training instructors was also explored. Methods A mixed methods research design was employed, using a Separate Pre-Post Samples Design and focus groups. Research was conducted in 15 Slovenian public elementary schools offering cardiopulmonary resuscitation training. Focus groups included training instructors and developers. Data was collected with a structured questionnaire from April to June 2018 and analyzed using univariate and bivariate analyses. The three focus groups were convened in September and October 2018. Content analysis of the discussion transcriptions was conducted. The sample included 764 schoolchildren aged 12.5-14.5 years before cardiopulmonary resuscitation training and 566 schoolchildren after training. Three non-homogeneous focus groups included eight cardiopulmonary resuscitation instructors. Results Significant progress in cardiopulmonary resuscitation knowledge was noted after training implementation, with the greatest progress seen in the youngest age group (mean age 12.5). The greatest increase after training was seen for the variables Attitude toward helping others (p = 0.001) and Self-confidence (p = 0.001). Analysis of the focus groups yielded two themes: (a) the effects of cardiopulmonary resuscitation training on schoolchildren, and (b) the systemic responsibility of the school system and professional bodies. Conclusions Significant progress in schoolchildren's cardiopulmonary resuscitation knowledge after training was established. Early introduction of training is recommended. Cardiopulmonary resuscitation knowledge raises awareness of the responsibility to help others and increases self-confidence to provide bystander cardiopulmonary resuscitation. It can be concluded that early cardiopulmonary resuscitation training for children is crucial. It should be a mandatory part of school curricula in those countries where cardiopulmonary resuscitation is not yet mandatory.